Nerve injury induces pain hypersensitivity and anxiety-related behaviours and is associated with amygdala activation in male mice - Siyuan Tong; Yuerong Chen; Zonglin Wu; Linbao Wang; YuXin Wei; Xirui Wang; Yuanyuan Wu (PLoS ONE, 2025)
Background Neuropathic pain is a common health problem, often accompanied by anxiety. The amygdala plays a crucial role in emotional processing and the basolateral amygdala (BLA) and the central amygdala (CeA) are primary components of the amygdala. The c-Fos is considered indicative of neuronal activation. We studied whether BLA and CeA are activated and their internal activation when chronic neuralgia occurs. Methods The spared nerve injury (SNI) model was employed for this investigation. Mechanical paw withdrawal thresholds (PWTs) were utilized for assessing pain hypersensitivity, followed by observation of anxiety-like behaviors using the elevated plus maze test (EPMT) and the open field test (OFT). The c-Fos in BLA and CeA were measured by immunofluorescence staining. Results We found that SNI mice exhibit pain hypersensitivity and anxiety-like behaviors. The expression of c-Fos in the BLA and CeA was upregulated in SNI mice. Besides, there were spatial differences in c-Fos expression between BLA and CeA. Conclusion The BLA and CeA showed activation in chronic pain and associated anxiety, and there were spatial differences in this activation. Targeting the amygdala may hold promise for treating chronic nerve pain with anxiety-like behaviors.